Resilience of Blockchain Overlay Networks - Paphitis, Aristodemos; Kourtellis, Nicolas; Sirivianos, Michael (My University, 2023)
Blockchain (BC) systems are highly distributed peer-to-peer networks that offer an alternative to centralized services and promise robustness to coordinated attacks. However, the resilience and overall security of a BC system rests heavily on the structural properties of its underlying peer-to-peer overlay. Despite their success, critical design aspects, connectivity properties, and interdependencies of BC overlay networks are still poorly understood. In this work, our aim was to fill this gap by analyzing the topological resilience of seven distinct BC networks. In particular, we probed and crawled these BC networks for 28 days. We constructed, at frequent intervals, connectivity graphs for each BC network consisting of all potential connections between peers. We analyze the structural graph properties of these networks and their topological resilience. We show that by targeting fewer than 10 highly connected peers, major BCs such as Bitcoin can be partitioned into disconnected components. Finally, we uncover a hidden overlap between different BC networks, where certain peers participate in more than one BC network. Our findings have serious implications for the robustness of the overall ecosystem of the BC network.
Keywords: Blockchain; P2P Networks; Robustness